2022
DOI: 10.1177/23259671221117802
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cannulated Screws for Primary Latarjet Procedures

Abstract: Background: Rapid consolidation of the bone block is paramount for the success of the Latarjet procedure. Noncannulated screws have shown satisfactory long-term bone block fusion, while cannulated screws are challenged with inferior mechanical properties and fusion rates. Purpose: To report outcomes of the Latarjet procedure using cannulated screws, notably bone block fusion and complication rates at 3 months, as well as clinical scores and return to sports at minimum 2 years postoperatively. Study Design: Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…9,13,14,35 In the future, this weakness of the open Latarjet procedure could be solved by using specifically designed screws or by switching to modern corticalbutton fixation of the graft. 12,31 Surprisingly, the BK group experienced a higher rate of osteoarthritis than the LT group (68% vs 38%, respectively), with grade 2 in 23% of the BK patients. Neviaser et al 25 reported an osteoarthritis rate of 47% after open Bankart at 17 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…9,13,14,35 In the future, this weakness of the open Latarjet procedure could be solved by using specifically designed screws or by switching to modern corticalbutton fixation of the graft. 12,31 Surprisingly, the BK group experienced a higher rate of osteoarthritis than the LT group (68% vs 38%, respectively), with grade 2 in 23% of the BK patients. Neviaser et al 25 reported an osteoarthritis rate of 47% after open Bankart at 17 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…The exclusion criteria were generalized joint laxity, multidirectional shoulder instability, other shoulder pathology associated with shoulder instability (such as rotator cuff tear), recurrence of dislocation after surgery, or postoperative shoulder stiffness defined by deficits in range of motion >20° in ≥2 planes when compared with the contralateral shoulder. 22…”
Section: Methodsmentioning
confidence: 99%
“…Research ethics committee approval (IRB00010835) was granted for this single-center retrospective analysis of 22 A sample of 68 healthy athletes with no history of upper extremity surgery or shoulder problems during the 6 months preceding the measurements were recruited for CG. The distribution of sex, laterality, type of sport, and sport involvement as well as mean age, body mass, and body height of the CG presented no significant differences compared with those variables in the 2 groups of patients.…”
Section: Participantsmentioning
confidence: 99%
“…More recently, arthroscopic bony Bankart repair arthroscopic bony Bankart repair [49] was introduced as a less invasive alternative to arthroscopic Latarjet, to treat anterior shoulder instability with traumatic glenoid defects, where the bone fragment is still present and could be sutured back onto the glenoid [4]. While arthroscopic bony Bankart repair demonstrated satisfactory bone union rates, it is associated with higher rates of recurrent instability compared to arthroscopic Latarjet [6,39,52,54], and may be insufficient to treat shoulders with irreparable ligamentous damage, attritional glenoid bone loss, or major bone deficiencies [15].…”
Section: Introductionmentioning
confidence: 99%